REVIEW OF RESEARCH ON FATIGUE LIFE EVALUATION FOR LARGE WELDED STRUCTURES (MT) - CAO LeiLei; WANG Yan; WANG LiuTao; SONG XuDing; GUO ChengChen (Jixie qiangdu)
Large welding structures have been widely used in various major equipment fields. Life evaluation of welding structures is very important for equipment safety.The fatigue life assessment methods including nominal stress method, notch stress method, hot spot stress method and equivalent structural stress method are summarized for large welded structures. The basic principles, advantages and disadvantages of various methods are compared and analyzed. The results show that the nominal stress method is simple and convenient, and can be used for simple welding structure analysis in various fields; the hot spot stress method is widely used in the field of marine ships; the notch stress method is complex in modeling and solving, and it can be used for both fatigue analysis of butt weld toe and weld root; the equivalent structural stress method is mesh insensitive, and can unify the application of various welded joints by a main SN curve, and has great potential application for engineering. The fatigue life assessment of large welded structures application in the fields of rail transit, ships, bridges, construction machinery and vehicles are introduced. The main difficulties and problems in the fatigue life prediction of the large welded structures at the emerging stage are analyzed. It provides references and ideas for the development of fatigue life evaluation methods for the large welded structures in the future.